The Attitudes of Older Users of Information Communication Technologies Towards Online Communication - Rapolienė, Gražina; Steponavičiūtė, Goda Marija; Gedvilaitė-Kordušienė, Margarita (Socialinė teorija, empirija, politika ir praktika, 2024)
Research suggests that the use of information and communication technologies (ICT), especially for communication purposes, can have a positive impact on the emotional health and subjective quality of life of older people. However, older people are little willing to engage in online communication. This article analyses the attitudes of older ICT users towards online communication. The study is based on 36 interviews with older ICT users and 9 interviews with people who encouraged them to use technology, conducted in 2022. The results of the study are in line with the theoretical Technology Acceptance Model. It is found that older people have positive attitudes towards online communication when they perceive its benefits. In contrast, public and private online communication are also criticized. Results reveal concerns that the rise of online communication is disrupting face-to-face communication, and that it is addictive and time-consuming. There are expressions of internalized ageism that such communication is more suitable for young people. The study results align with the Media Richness Theory, with older people emphasising the irreplaceability of live communication as the richest form of communication.
Keywords: information and communication technologies (ICT); older people; online communication; attitudes